The Influence of Work Motivation on Employee Performance in the Hospitality Industry - Nurmal Nurmal; Sriwanti Belani; Muh Agil; Aryan Septia Budi; Agustiawan Agustiawan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
The hospitality industry faces increasingly fierce competition, requiring companies to improve service quality through effective human resource management. One challenge that often arises is low work motivation, which affects employee performance. This problem is crucial because employees are the spearhead in providing service to customers. Therefore, this study aims to analyze the effect of work motivation on employee performance in the hospitality industry. This study was conducted at the Ada Hotel, involving eight employees. The research method used was a quantitative method with data collection techniques using a work motivation and employee performance questionnaire. The data obtained were then analyzed using simple regression to determine the effect of motivation on employee performance. The results showed that work motivation has a positive and significant effect on employee performance. Employees who have high motivation tend to provide better service and support the achievement of organizational goals. Therefore, increasing work motivation is an important factor that needs to be considered by hotel management to support the optimization of employee performance